Flooding phenomena in two immiscible liquids system : conceptual approach - Sandaray, Parthiban (2013)
The use of the liquid separating equilibrium has recently become favourable as the temperature window for the biodiesel synthesis does not require reaching the distillation thermodynamic state. This study is mainly to characterize the flooding properties in liquid-liquid system of palm oil and ethanol. The key parameters, the Sauter diameter of ethanol and oil droplet in the excess oil or ethanol phase, coalescence factor of excess volume in various ratios, and hydrodynamics in cylindrical viscometer carried on. Firstly, to measure the Sauter diameter of ethanol in excess oil done in laboratory by self-modified syringe tube by releasing droplet form the bottom of measuring cylinder. For the second experiment, several ratios of oil to ethanol prepared mixed vigorously for 20 minutes at 450C. The time for settlement and height of two layers formed recorded. Finally for the third experiment, several ratios of oil to ethanol prepared and mixed vigorously for 20 minutes at 450C and the mixture tested for the viscosity, shear rate and rpm in viscometer. Average, 0.002m Sauter diameter of ethanol and oil droplet measured at 7.29x10-3 m/s and 0.73 m/s of velocity, suggesting that the aperture of the plate would be at least 0.005m if either ethanol or oil to be the dispersed phase. In the meantime, the result of liquids mixing shows that the solubility of ethanol increased proportionally with the volume of ethanol at 450C. At low concentration of ethanol, however, the slope decreased due to the formation of emulsion phase. The key parameters that influences the flooding in the hydrodynamics are viscosity and agitation speed. To the flooding point of view, low viscosity would make the flow of the liquid flow easier. The increase of agitation speed increases the chance of flooding in the viscometer.